Terapia fotodinâmica antimicrobiana sobre biofilmes dentais utilizando luz não-coerente e azul de orto-toluidina: estudo In vitro - Silva, Héllen Súzany Freire (2024)
Dental caries is a sugar-dependent biofilm disease, it is closely related to the presence of bacterial biofilm on the surface of the teeth and is one of the most prevalent chronic diseases in the world. Photodynamic Antimicrobial Therapy (PDT) using ozonated water as a diluent for the photosensitizing agent may represent a new strategy for the prevention and/or treatment of biofilm-dependent diseases due to its antimicrobial potential associated with the production of reactive oxygen species. The aim of this research was to evaluate the antimicrobial effect of conventional TFA and TFA using ozonated water as a sensitizer diluent on dental biofilms of Streptococcus mutans through an in vitro study. To this end, hydroxyapatite discs and blocks of human enamel were used as substrates for the formation of S. mutans UA159 biofilms in the presence of sucrose. All experiments were performed in duplicate. Three biological replicates were performed for each experiment. Initially, different biofilm formation times (24 h, 72 h and 120 h) were tested on hydroxyapatite discs and based on the results obtained, biofilms with 24 h of formation were tested on human enamel. The light source used for PDT was a light-emitting diode with a predominant wavelength of λ=630 nm, light intensity of 150 mW/cm2±10% and energy density of 70.86 J/cm2. The photosensitizing agent used was orthotoluidine blue (TBO) at a concentration of 100 μg/ml. In all situations, comparisons were made between groups using the dye prepared in water (TBO) and in ozonated water (TBO+OZ). Chlorhexidine 0.12% was used as control group. The treatment conditions to which the biofilms were subjected were: sensitization with TBO+OZ and exposure to light (S+OZ+L+) and sensitization with TBO and exposure to light (S+OZ-L+); non-exposure to TBO+OZ or light (S-OZ+L-) and non-exposure to TBO or light (S-OZ-L-); exposure only to TBO+OZ (S+OZ+L-) and exposure only to TBO (S+OZ-L-); and finally exposure only to light in the presence of ozonated water (S-OZ+L+) or exposure only to light in the absence of ozonated water (S-OZ-L+). For the groups that were exposed to light (S+OZ+L+, S+OZ-L+, S-OZ+L+ e S-OZ-L+), a 5-minute exposure time was used (70.86 Jcm-2). GraphPad Prism software, version 10.2, was used for statistical analysis. Normality distribution was verified using the Kolmogorov–Smirnov test. To determine the difference between the values of the test groups and the controls, one-way ANOVA analysis of variance was performed, followed by the Brown-Forsythe test. As a result, in biofilms with 24 h of formation, both on hydroxyapatite discs and on human enamel, a reduction of more than 5 logs was obtained in the groups S+OZ+L+ e S+OZ-L+ (where conventional treatment with PDT was performed), showing a statistical difference (p< 0.0001) when compared to the other groups. For biofilms with 72 h and 120 h of formation on hydroxyapatite discs, no statistical differences were found between the treatments tested. No significant differences were observed in cell viability using conventional photodynamic therapy (S+OZ-L+) and ozonated water (S+OZ+L+). Thus, both conventional TFA and TFA with ozonated water as a TBO diluent, were effective in reducing the number of viable cells in 24-hour Streptococcus mutans biofilms, formed in vitro on hydroxyapatite discs and on human enamel blocks.